Prevalence Of Hypertension Among Rural and Urban Population in Southern Rajasthan - Antima Galav; Rekha Bhatanagar; Suresh Chandra Meghwal; Manish Jain (Medsci Publications, 2015)
Introduction: Hypertension (HTN) is one of the most common cardiovascular diseases and an important cause of morbidity and mortality worldwide. Estimating the prevalence of hypertension in both the urban and rural populations is very crucial as this forms the basis for planning of primary and secondary prevention of hypertension. Objective of the study was to estimate and com- pare the prevalence of hypertension in urban and rural adult population. Method: A cross-sectional study was carried out from March- 2013 to August-2013 in Udaipur, Rajasthan to compare the preva- lence of hypertension in urban and rural adult population. Hy- pertension was defined according to JNC VII criteria. Results: Hypertension was present in 32. 67% subjects in urban and 18. 67% in rural area. The prevalence was found to steadily increase with age. There was no significant difference in the prev- alence of hypertension between males and females in both areas. Among urban hypertensives 87. 76% led a sedentary lifestyle, 45. 92% were overweight and 14. 28% were obese. Conclusion: Significantly higher prevalence of hypertension was found in urban area. Majority of hypertensive had a sedentary life-style in both rural and urban areas. Adopting a healthy life- style is critical for the prevention of hypertension and an indis- pensable part of managing it.